Method for testing and analyzing types and contents of binders

Through thermogravimetric analysis and differential thermogravimetric analysis combined with peak fitting treatment, the problem of adhesive composition analysis of the negative electrode sheet of lithium-ion battery is solved, and the accurate test of the types and content of adhesives in unknown electrode sheets is achieved, which improves the battery Analytical capabilities of R&D.

CN119269320APending Publication Date: 2025-01-07中汽新能(天津)电池科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411280072.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art cannot effectively reversely analyze the components of the adhesive in the negative electrode sheet of lithium-ion battery, making it difficult to understand the real situation and composition of the electrode sheet, affecting the electrochemical performance of the battery.

Method used

Thermogravimetric analysis combined with differential thermogravimetric analysis was used to determine the type of binder by TG and DTG curves, and the characteristic peaks of the binder were separated by peak fitting treatment to calculate the content of binder.

Benefits of technology

Accurate testing of the types and content of binders in unknown electrode sheets is achieved, important reference information for the research and development of lithium-ion batteries, and improved the analytical ability of battery production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119269320A_ABST
    Figure CN119269320A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of battery testing, and particularly relates to a method for testing and analyzing types and contents of binders. The binder type test analysis method comprises the following steps: carrying out thermogravimetric analysis on a binder-containing sample to be tested to obtain a thermogravimetric TG curve and a differential thermogravimetric DTG curve; and judging the type of the binder according to the obtained TG curve or DTG curve of the sample to be detected. According to the method disclosed by the invention, the peak of the CMC can be effectively separated from the peak of the by-product generated at the negative electrode after formation through the peak-dividing fitting treatment, so that the later thermal weight loss data extraction and integral calculation can be conveniently carried out.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of battery testing, and in particular relates to a method for testing and analyzing the type and content of a binder. Background Art

[0002] With the continuous innovation of new energy material research and development technology, lithium-ion batteries with advantages such as low carbon and environmental protection, high energy density, and wide operating temperature range have received widespread attention. Binders, as inactive ingredients in lithium-ion battery electrode sheets, are one of the important materials that must be used to prepare lithium-ion battery electrode sheets. The main function of the binder is to connect the electrode active material, the conductive agent, and the electrode current collector so that they have overall connectivity, thereby reducing the impedance of the electrode and better stabilizing the electrode sheet structure. Although the binder accounts for a small proportion of the battery, it is the main source of the mechanical properties of the entire electrode, and has an important influence on the production process of the electrode and the electrochemical performance of the battery. The negative electrode sheet usually uses polymers such as carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and polyacrylic acid (PAA) as binders. Low content will lead to low bonding between the active material, the conductive agent, and the current collector, and the electrode sheet is prone to powdering and breaking. Excessive binder content will increase the internal resistance of the battery and reduce the electrochemical performance of the battery. Therefore, it is necessary to evaluate the composition of the binder in the unknown electrode in order to understand the actual situation of the electrode and improve the analytical ability of the electrode composition and formula analysis. However, there is currently no method for reverse analysis of the binder composition in the negative electrode. Summary of the invention

[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for testing and analyzing the type and content of a binder.

[0004] To achieve the above object, the technical solution adopted by the present invention is:

[0005] A method for testing the type of a binder comprises the following steps: performing thermogravimetric analysis on a sample to be tested containing the binder to obtain a thermogravimetric TG curve and a differential thermogravimetric DTG curve; and judging the type of the binder by the TG curve or DTG curve of the sample to be tested.

[0006] The method for determining the type of binder is as follows: the corresponding weight loss temperature interval of the binder component in the TG curve contains an inflection point, the corresponding weight loss temperature interval of the binder component in the DTG curve contains a characteristic peak, or the DTG curve is peak-fitted according to the corresponding weight loss temperature interval of the binder component.

[0007] The binder component includes one or a mixture of CMC, SBR and PAA.

[0008] The corresponding weight loss temperature range of CMC is 200℃-300℃, the corresponding weight loss temperature range of SBR is 380℃-500℃, and the corresponding weight loss temperature range of PAA is 320℃-380℃.

[0009] The setting conditions of thermogravimetric analysis are: heating rate of 5-20℃ / min, preferably 10℃ / min; heating range of 50-600℃; nitrogen atmosphere is introduced to start the test, and the atmosphere flow rate is 50-200mL / min; preferably 100mL / min; preferably, a constant temperature section of 10min is added at 100℃ to eliminate the influence of moisture in the electrode powder.

[0010] The test sample is prepared in the following manner: after fully discharging the test battery with unknown electrode formula, the battery is dissected to disassemble the electrode, the residual electrolyte on the surface of the electrode is removed by soaking with DMC, and then the electrode powder scraped off after drying in an oven is used as the test sample.

[0011] The present invention also includes a test and analysis method for binder content, comprising the following steps: 1) obtaining the type of binder through the test and analysis method for the type of binder; 2) selecting a formula with a known binder content of the same type of binder as a reference sample according to the binder type obtained in step 1) to perform thermogravimetric analysis to obtain a thermogravimetric TG curve and a differential thermogravimetric DTG curve; 3) performing peak fitting processing on the DTG curve of the reference sample to obtain the corresponding relationship between the peak area of ​​the fitting peak corresponding to different binders of the reference sample and the binder content; 4) performing peak fitting processing on the DTG curve of the sample to be tested to obtain the peak area of ​​the fitting peak corresponding to the binder of the sample to be tested; and obtaining the binder content of the sample to be tested through the peak area of ​​the sample to be tested.

[0012] The conditions for peak fitting in steps 3) and 4) are independently: the weight loss temperature range corresponding to CMC is 200°C-300°C, the weight loss temperature range corresponding to SBR is 380°C-500°C, and the weight loss temperature range corresponding to PAA is 320°C-380°C.

[0013] The calculation method of step 4) is: CMC content M = a1 / a*m*100%, SBR content N = b1 / b*n*100%; PAA content Q = c1 / c*n*100%; wherein a1, b1, c1 are respectively the fitted peak areas of CMC, SBR, and PAA in the sample to be tested after peak fitting; a, b, c are respectively the fitted peak areas of CMC, SBR, and PAA in the reference sample after peak fitting, and m, n, and p are respectively the contents of CMC, SBR, and PAA in the formula of the reference sample.

[0014] The reference sample and the sample to be tested were prepared in the same way; the reference sample and the sample to be tested were subjected to the same thermogravimetric analysis conditions.

[0015] For the present invention, it should be noted that when selecting a reference sample, the type of binder contained in it must be the same as the type of binder contained in the sample to be tested. When the type of binder contained in the sample to be tested is the same, the reference sample does not need to be tested repeatedly.

[0016] For the present invention, it should be noted that the peak fitting process is a conventional data processing technology, which is generally performed using peakfit software. In the specific operation, by importing the DTG data, selecting the temperature range, such as 100°C-600°C, setting the peak type and other fitting parameters, the above software will be used to perform fitting through multiple iterative calculations, and the final fitting effect can be analyzed and judged by determining the coefficient r2 (the closer to 1, the better the fit) and the standard error SE (the smaller the better). In the present invention, since the peak fitting process is similar to the prior art, it will not be described in detail here.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The technical solution of the present application mainly adopts the process of peak fitting. When materials with different thermal weight loss are detected by a thermogravimetric analyzer, since a layer of SEI film and some byproducts will be formed on the surface of the negative electrode sheet of the battery after formation, these byproducts and the characteristic peaks of CMC are wrapped together and cannot be effectively separated. Therefore, it is impossible to accurately perform integral calculation on the characteristic peaks of CMC. For this reason, the present invention can effectively separate the peak of CMC from the peak of the byproduct generated at the negative electrode after formation through peak fitting processing, so as to facilitate the subsequent thermal weight loss data extraction and integral calculation.

[0019] The present invention provides a testing and analysis method for the type and content of a negative electrode sheet binder for a lithium ion battery, which can perform reverse analysis on the negative electrode sheet binder in a lithium ion battery with an unknown formula, and provide benchmarking reference information for battery research and development, which has great significance for production practice. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 TG and DTG graphs of the sample to be tested in Example 1 of the present invention.

[0021] Figure 2 This is the DTG peak fitting diagram of the sample to be tested in Example 1 of the present invention.

[0022] Figure 3 TG and DTG graphs of the reference sample in Example 1 of the present invention.

[0023] Figure 4 This is the DTG peak fitting diagram of the reference sample in Example 1 of the present invention.

[0024] Figure 5TG and DTG graphs of the sample to be tested in Example 2 of the present invention.

[0025] Figure 6 This is the DTG peak fitting diagram of the sample to be tested in Example 2 of the present invention.

[0026] Figure 7 TG and DTG graphs of the sample to be tested in Example 3 of the present invention.

[0027] Figure 8 This is the DTG peak fitting diagram of the sample to be tested in Example 3 of the present invention.

[0028] Fig. 9 TG and DTG graphs of the reference sample in Example 3 of the present invention.

[0029] Fig.10 This is the DTG peak fitting diagram of the reference sample in Example 3 of the present invention. DETAILED DESCRIPTION

[0030] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and the best embodiments.

[0031] Example 1

[0032] A method for testing and analyzing the binder content of a lithium ion battery negative electrode sheet comprises the following steps:

[0033] 1. Obtain the sample to be tested, and perform thermogravimetric testing and peak separation on it.

[0034] ① Obtain the sample to be tested: The sample to be tested is a battery to be tested with an unknown electrode formula. After the battery is fully discharged, the battery is dissected to disassemble the negative electrode sheet, and the electrolyte remaining on the surface of the negative electrode sheet is removed by soaking with DMC, and then the negative electrode powder is scraped off after drying in an oven.

[0035] ② Perform thermogravimetric test on the sample to be tested to obtain the thermogravimetric TG curve and differential thermogravimetric DTG curve.

[0036] The obtained sample to be tested is placed in a crucible, and then placed in a thermogravimetric analyzer, and the thermogravimetric analysis software is started for thermogravimetric analysis, so as to obtain an accurate thermogravimetric (TG) curve and a first-order differential thermogravimetric curve of the sample to be tested. The first-order differential thermogravimetric data of the sample to be tested is taken as the inverse to draw a curve (DTG curve) for subsequent data processing, such as Figure 1 shown.

[0037] Thermogravimetric analysis set the heating rate to 10°C / min and the heating range to 50-600°C. A constant temperature section of 10 min was added at 100°C to eliminate the influence of moisture in the pole powder. The test was started by introducing nitrogen atmosphere with an atmosphere flow rate of 100 mL / min.

[0038] For the obtained Figure 1 The DTG curve of the sample to be tested is analyzed. The temperature range of weight loss of CMC is 200℃-300℃, and the temperature range of weight loss of SBR is 380℃-500℃. Therefore, it is judged that the types of binders contained are CMC and SBR. It can also be processed by peak fitting, such as step ③.

[0039] ③Perform peak fitting processing on the DTG curve of the sample to be tested.

[0040] For the obtained Figure 1 The DTG curve of the sample to be tested is subjected to peak fitting processing to obtain independent fitting curves of different fitting peaks corresponding to each binder and by-product after formation in the sample to be tested, and the independent fitting curves of different fitting peaks are attributed and distinguished according to the temperature range corresponding to the weight loss of the binder (the temperature range of weight loss of CMC is 200°C-300°C, and the temperature range of weight loss of SBR is 380°C-500°C). According to the peak type of the DTG curve and the number of peaks, the binders in the sample to be tested are determined to be CMC and SBR, and the following is obtained: Figure 4 The fitting peaks 1, 2 and 3 corresponding to the by-products, CMC and SBR in the sample to be tested are shown. Figure 4 A is the DTG curve measured by the thermogravimetric analyzer, B is the fitting curve, C is the curve belonging to the by-product obtained after peak fitting according to the measured DTG curve A of the sample, D is the curve belonging to CMC obtained after peak fitting according to the measured DTG curve A of the sample, and E is the curve belonging to SBR obtained after peak fitting according to the measured DTG curve A of the sample. B is the fitting curve after the addition of fitting peaks C, D, and E, which is in good agreement with the first-order differential curve A of the measured sample. The independent fitting data of CMC and SBR corresponding to the sample to be tested are integrated respectively to obtain the peak areas of the corresponding CMC and SBR fitting peaks, and the fitting peak area a1 of CMC in the sample to be tested is 0.52%, and the fitting peak area b1 of SBR is 1.83%.

[0041] 2. According to the type of binder in the sample to be tested, obtain a reference sample with a known formula of the same type of binder, and perform thermogravimetric testing and peak separation on it to establish a benchmark for quantitative calculation of the binder.

[0042] ① Obtain a reference sample of known formula, which contains two binders: CMC and SBR.

[0043] The reference sample is a battery with a known formula after formation, and the negative electrode powder is scraped after being disassembled, washed with DMC and dried. The content m of CMC in the reference sample with a known formula is 1%, the content n of SBR is 1.5%, and the content of the main carbon material and the conductive agent accounts for 97.5%.

[0044] ②Perform thermogravimetric test on the reference sample.

[0045] The obtained reference sample is placed in a crucible, and then placed in a thermogravimetric analyzer, and the thermogravimetric analysis software is started for thermogravimetric analysis, so as to obtain an accurate thermogravimetric (TG) curve and a first-order differential thermogravimetric curve of the reference sample. The first-order differential thermogravimetric data of the reference sample is plotted by taking the inverse number to draw a curve (DTG curve) for subsequent data processing, such as Figure 3 shown.

[0046] Among them, when testing the reference sample, the test conditions set by the thermogravimetric analyzer are consistent with those of the sample to be tested. The heating rate is set to 10℃ / min, the heating range is 50-600℃, and a constant temperature section of 10min is added at 100℃ to eliminate the influence of moisture in the pole powder. The test is started by introducing nitrogen atmosphere, and the atmosphere flow rate is 100mL / min.

[0047] ③Perform peak fitting processing on the DTG curve of the reference sample.

[0048] For the obtained Figure 3 The DTG curve of the reference sample of the known formula shown in the figure is subjected to peak fitting processing to obtain independent fitting curves of different fitting peaks corresponding to each binder and by-product after formation in the reference sample, and the independent fitting curves of different fitting peaks are distinguished by the binder attribution according to the temperature range corresponding to the weight loss of the binder (the temperature range of weight loss of CMC is 200℃-300℃, and the temperature range of weight loss of SBR is 380℃-500℃), and the following is obtained: Figure 4 The fitting peaks 1, 2 and 3 corresponding to the by-products, CMC and SBR in the reference sample are shown. Figure 4A is the DTG curve measured by the thermogravimetric analyzer reference sample, B is the fitting curve, C is the curve belonging to the by-product obtained after peak fitting based on the DTG curve A of the sample, D is the curve belonging to CMC obtained after peak fitting based on the measured DTG curve A of the sample, and E is the curve belonging to SBR obtained after peak fitting based on the measured DTG curve A of the sample. B is the fitting curve after the addition of fitting peaks C, D and E. It can be seen that it is in good agreement with the first-order differential curve A of the measured reference sample. The independent fitting data of CMC and SBR corresponding to the reference sample are integrated respectively to obtain the fitting peak area a of 0.33% for CMC with a content m of 1% and the fitting peak area b of 1.78% for SBR with a content n of 1.5% in the reference sample, which is used as the basis for the subsequent quantitative calculation of the binder in the negative electrode sheet containing CMC and SBR binders.

[0049] 3. Calculate the binder content in the sample to be tested.

[0050] Based on the known fitting peak area a of CMC with a content m of 1% in the reference sample being 0.33%, the fitting peak area b of SBR with a content n of 1.5% being 1.78%, the fitting peak area a1 of CMC in the test sample being 0.52%, and the fitting peak area b1 of SBR being 1.83%, the content of CMC (M) and the content of SBR (N) in the test sample being calculated.

[0051] The content of CMC is M = a1 / a*m*100% = 1.57%, the content of SBR is N = b1 / b*n*100% = 1.55%, and the content of carbon main material and conductive agent accounts for 96.88%. Therefore, the ratio of the electrode of the sample to be tested is carbon main material + conductive agent: CMC: SBR = 96.88:1.57:1.55.

[0052] Example 2

[0053] A method for testing and analyzing the binder content of a lithium ion battery negative electrode sheet comprises the following steps:

[0054] 1. Obtain the sample to be tested, and perform thermogravimetric testing and peak separation on it.

[0055] ① Obtain the sample to be tested.

[0056] The sample to be tested is a battery to be tested with an unknown electrode sheet formula. After the battery is fully discharged, the battery is dissected to disassemble the negative electrode sheet, and the electrolyte remaining on the surface of the negative electrode sheet is removed by soaking with DMC, and then the negative electrode powder is scraped after drying in an oven;

[0057] ② Carry out thermogravimetric test on the samples to be tested.

[0058] The obtained sample to be tested is placed in a crucible, and then placed in a thermogravimetric analyzer, and the thermogravimetric analysis software is started for thermogravimetric analysis, so as to obtain an accurate thermogravimetric (TG) curve and a first-order differential thermogravimetric curve of the sample to be tested. The first-order differential thermogravimetric data of the sample to be tested is taken as the inverse to draw a curve (DTG curve) for subsequent data processing, such as Figure 5 shown.

[0059] Among them, the test conditions set by the thermogravimetric analyzer when testing the sample to be tested are consistent with the sample to be tested in Example 1. The heating rate is set to 10°C / min, the heating range is 50-600°C, and a constant temperature section of 10min is added at 100°C to eliminate the influence of moisture in the pole powder. The test is started by introducing a nitrogen atmosphere with an atmosphere flow rate of 100mL / min.

[0060] ③Perform peak fitting processing on the DTG curve of the sample to be tested.

[0061] For the obtained Figure 5 The DTG curve of the sample to be tested is subjected to peak fitting processing to obtain independent fitting curves of different fitting peaks corresponding to each binder and by-product after formation in the sample to be tested, and the independent fitting curves of different fitting peaks are attributed and distinguished according to the temperature range corresponding to the weight loss of the binder (the temperature range of weight loss of CMC is 200°C-300°C, and the temperature range of weight loss of SBR is 380°C-500°C). According to the peak type of the TG curve and the number of peaks, the binders in the sample to be tested are determined to be CMC and SBR, and the following is obtained: Figure 6 The fitting peaks 1, 2 and 3 corresponding to the by-products, CMC and SBR in the sample to be tested are shown. Figure 6 A is the DTG curve measured by the thermogravimetric analyzer, B is the fitting curve, C is the curve belonging to the by-product obtained after peak fitting based on the measured DTG curve A of the sample, D is the curve belonging to CMC obtained after peak fitting based on the measured DTG curve A of the sample, and E is the curve belonging to SBR obtained after peak fitting based on the measured DTG curve A of the sample. B is the fitting curve after the addition of fitting peaks C, D, and E, which is in good agreement with the first-order differential curve A of the measured sample. The independent fitting data of CMC and SBR corresponding to the sample to be tested are integrated respectively to obtain the peak areas of the corresponding CMC and SBR fitting peaks, and the fitting peak area a1 of CMC in the sample to be tested is 0.56%, and the fitting peak area b1 of SBR is 1.91%.

[0062] 2. Select the reference sample in Example 1 as the basis for the quantitative calculation of the binder of the subsequent samples to be tested.

[0063] 3. Calculate the binder content in the sample to be tested.

[0064] Based on the known fitting peak area a of CMC with a content m of 1% in the reference sample of 0.33%, the fitting peak area b of SBR with a content n of 1.5% of 1.78%, the fitting peak area a1 of CMC in the test sample of 0.56% and the fitting peak area b1 of SBR of 1.91%, the content of CMC (M) and the content of SBR (N) in the test sample were calculated.

[0065] The content of CMC is M = a1 / a*m*100% = 1.70%, and the content of SBR is N = b1 / b*n*100% = 1.61%. The content of carbon main material and conductive agent accounts for 96.88%. Therefore, the ratio of the electrode of the sample to be tested is carbon main material + conductive agent: CMC: SBR = 96.69:1.70:1.61

[0066] Example 3

[0067] 1. Obtain the sample to be tested, and perform thermogravimetric testing and peak separation on it.

[0068] ① Obtain the sample to be tested.

[0069] The sample to be tested is a battery to be tested with an unknown electrode sheet formula. After the battery is fully discharged, the battery is dissected to disassemble the negative electrode sheet, and the electrolyte remaining on the surface of the negative electrode sheet is removed by soaking with DMC, and then the negative electrode powder is scraped after drying in an oven;

[0070] ② Carry out thermogravimetric test on the samples to be tested.

[0071] The obtained sample to be tested is placed in a crucible, and then placed in a thermogravimetric analyzer, and the thermogravimetric analysis software is started for thermogravimetric analysis, so as to obtain an accurate thermogravimetric (TG) curve and a first-order differential thermogravimetric curve of the sample to be tested. The first-order differential thermogravimetric data of the sample to be tested is taken as the inverse to draw a curve (DTG curve) for subsequent data processing, such as Figure 7 shown.

[0072] Among them, the test conditions set by the thermogravimetric analyzer when testing the sample to be tested are consistent with the sample to be tested in Example 1. The heating rate is set to 10°C / min, the heating range is 50-600°C, and a constant temperature section of 10min is added at 100°C to eliminate the influence of moisture in the pole powder. The test is started by introducing a nitrogen atmosphere with an atmosphere flow rate of 100mL / min.

[0073] ③Perform peak fitting processing on the DTG curve of the sample to be tested.

[0074] For the obtained Figure 7The DTG curve of the sample to be tested is subjected to peak fitting processing to obtain independent fitting curves of different fitting peaks corresponding to each binder and by-product after formation in the sample to be tested, and the independent fitting curves of different fitting peaks are attributed and distinguished according to the temperature range corresponding to the weight loss of the binder (the temperature range of CMC weight loss is 200°C-300°C, the temperature range of SBR weight loss is 380°C-500°C, and the temperature range of PAA weight loss is 320°C-380°C). According to the peak type of the TG curve and the number of peaks, the binders in the sample to be tested are determined to be CMC, SBR and PAA, and the following is obtained: Figure 8 The fitting peaks 1, 2, 3 and 4 corresponding to the by-products, CMC, PAA and SBR in the test samples are shown. Figure 8 A is the DTG curve measured by the thermogravimetric analyzer, B is the fitting curve, C is the curve belonging to the by-product obtained after peak fitting according to the measured DTG curve A of the sample, D is the curve belonging to CMC after peak fitting according to the measured DTG curve A of the sample, E is the curve belonging to PAA after peak fitting according to the measured DTG curve A of the sample, and F is the curve belonging to SBR after peak fitting according to the measured DTG curve A of the sample. B is the fitting curve after the addition of fitting peaks C, D, E and F, which is well consistent with the first-order differential curve A of the measured sample to be tested. The independent fitting data of CMC, SBR and PAA corresponding to the sample to be tested are integrated respectively to obtain the peak areas of the corresponding CMC, SBR and PAA fitting peaks. The fitting peak area a1 of CMC in the sample to be tested is 0.86%, the fitting peak area b1 of SBR is 1.03%, and the fitting peak area c1 of PAA is 0.68%.

[0075] 2. According to the type of binder in the sample to be tested, obtain a reference sample with a known formula of the same type of binder, and perform thermogravimetric testing and peak separation on it to establish a benchmark for quantitative calculation of the binder.

[0076] ① Obtain a reference sample with a known formula, which contains three binders: CMC, SBR and PAA.

[0077] The reference sample is a battery with a known formula after formation, and the negative electrode powder is scraped after being disassembled, washed and dried with DMC.

[0078] Among the reference samples with known formula, the content m of CMC is 0.6%, the content n of SBR is 0.7%, the content p of PAA is 1.30%, and the content of carbon main material and conductive agent accounts for 97.4%.

[0079] ②Perform thermogravimetric test on the reference sample.

[0080] The obtained reference sample is placed in a crucible, and then placed in a thermogravimetric analyzer, and the thermogravimetric analysis software is started for thermogravimetric analysis, so as to obtain an accurate thermogravimetric (TG) curve and a first-order differential thermogravimetric curve of the reference sample. The first-order differential thermogravimetric data of the reference sample is plotted by taking the inverse number to draw a curve (DTG curve) for subsequent data processing, such as Fig. 9 shown.

[0081] Among them, the test conditions set by the thermogravimetric analyzer when testing the reference sample are consistent with the sample to be tested in Example 1. The heating rate is set to 10°C / min, the heating range is 50-600°C, and a constant temperature section of 10min is added at 100°C to eliminate the influence of moisture in the pole powder. The test is started by introducing a nitrogen atmosphere with an atmosphere flow rate of 100mL / min.

[0082] ③Perform peak fitting processing on the DTG curve of the reference sample.

[0083] For the obtained Fig. 9 The DTG curve of the reference sample of the known formula shown in the figure is subjected to peak fitting processing to obtain independent fitting curves of different fitting peaks corresponding to each binder and the by-product after formation in the reference sample, and the independent fitting curves of different fitting peaks are attributed and distinguished according to the temperature range corresponding to the weight loss of the binder (the temperature range of weight loss of CMC is 200℃-300℃, the temperature range of weight loss of SBR is 380℃-500℃, and the temperature range of weight loss of PAA is 320℃-380℃), and the following is obtained: Fig.10 The fitting peaks 1, 2, 3 and 4 corresponding to the by-products, CMC, PAA and SBR in the reference sample are shown. Fig.10 A is the DTG curve measured by the thermogravimetric analyzer reference sample, B is the fitting curve, C is the curve belonging to the by-product obtained after peak fitting based on the DTG curve A of the sample, D is the curve belonging to CMC obtained after peak fitting based on the measured DTG curve A of the sample, E is the curve belonging to PAA obtained after peak fitting based on the measured DTG curve A of the sample, and F is the curve belonging to SBR obtained after peak fitting based on the measured DTG curve A of the sample. B is the fitting curve after the addition of fitting peaks C, D, E and F, which can be seen to be in good agreement with the first-order differential curve A of the measured reference sample. The independent fitting data of CMC, SBR and PAA corresponding to the reference sample were integrated respectively to obtain the fitting peak area a1 of 0.66% for CMC with a content m of 0.6%, the fitting peak area b1 of 0.93% for SBR with a content n of 0.7%, and the fitting peak area c1 of 0.52% for PAA with a content p of 1.3% in the reference sample, which were used as the basis for the subsequent quantitative calculation of the binder in the negative electrode sheet containing CMC, SBR and PAA binders.

[0084] 3. Calculate the binder content in the sample to be tested.

[0085] Based on the known fitting peak area a of CMC with a content m of 0.6% in the reference sample, which is 0.66%, the fitting peak area b of SBR with a content n of 0.7% is 0.93%, and the fitting peak area c of PAA with a content p of 1.3% is 0.52%, the fitting peak area a1 of CMC in the test sample is 0.86%, the fitting peak area b1 of SBR is 1.03%, and the fitting peak area c1 of PAA is 0.68%, the content of CMC (M), the content of SBR (N) and the content of PAA (Q) in the test sample are calculated.

[0086] The content of CMC is M = a1 / a*m*100% = 0.79%, the content of SBR is N = b1 / b*n*100% = 0.78%, and the content of PAA is Q = c1 / c*n*100% = 1.69%, so the content of carbon main material and conductive agent accounts for 96.75%. Therefore, the formula of the electrode of the sample to be tested is carbon main material + conductive agent: CMC: SBR: PAA = 96.75: 0.79: 0.78: 1.69.

[0087] In summary, the technical solution of the present application mainly adopts the peak fitting process. When materials containing different thermal weight loss are detected by a thermogravimetric analyzer, since a layer of SE I film and some byproducts will be formed on the surface of the negative electrode sheet of the battery after formation, these byproducts and the characteristic peaks of CMC are wrapped together and cannot be effectively separated. Therefore, it is impossible to accurately integrate and calculate the characteristic peaks of CMC. For this reason, the present invention can effectively separate the peak of CMC from the peak of the byproduct generated at the negative electrode after formation through the peak fitting process, so as to facilitate the subsequent thermal weight loss data extraction and integration calculation.

[0088] The present invention provides a testing and analysis method for the type and content of a negative electrode sheet binder for a lithium ion battery, which can perform reverse analysis on the negative electrode sheet binder in a lithium ion battery with an unknown formula, and provide benchmarking reference information for battery research and development, which has great significance for production practice.

[0089] Without departing from the principle of the present invention, several improvements and modifications may be made, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for testing the type of adhesive, characterized in that: The method comprises the following steps: performing thermogravimetric analysis on a sample to be tested containing a binder to obtain a thermogravimetric TG curve and a differential thermogravimetric DTG curve; and judging the type of the binder by the TG curve or DTG curve of the sample to be tested.

2. The method for testing the type of adhesive according to claim 1, characterized in that: The method for determining the type of binder is as follows: the corresponding weight loss temperature interval of the binder component in the TG curve contains an inflection point, the corresponding weight loss temperature interval of the binder component in the DTG curve contains a characteristic peak, or the DTG curve is peak-fitted according to the corresponding weight loss temperature interval of the binder component.

3. The method for testing the type of adhesive according to claim 2, characterized in that: The binder component includes one or a mixture of CMC, SBR and PAA.

4. The method for testing the type of adhesive according to claim 3, characterized in that: The corresponding weight loss temperature range of CMC is 200℃-300℃, the corresponding weight loss temperature range of SBR is 380℃-500℃, and the corresponding weight loss temperature range of PAA is 320℃-380℃.

5. The method for testing and analyzing the type of adhesive according to claim 1, characterized in that: The setting conditions of thermogravimetric analysis are: heating rate of 5-20℃ / min, preferably 10℃ / min; heating range of 50-600℃; nitrogen atmosphere is introduced to start the test, and the atmosphere flow rate is 50-200mL / min; preferably 100mL / min; preferably, a constant temperature section of 10min is added at 100℃ to eliminate the influence of moisture in the electrode powder.

6. The method for testing and analyzing the type of adhesive according to claim 1, characterized in that: The test sample is prepared in the following manner: after fully discharging the test battery with unknown electrode formula, the battery is dissected to disassemble the electrode, the residual electrolyte on the surface of the electrode is removed by soaking with DMC, and then the electrode powder scraped off after drying in an oven is used as the test sample.

7. A method for testing and analyzing the content of a binder, characterized in that: The method comprises the following steps: 1) obtaining the type of the adhesive by the test and analysis method for the type of the adhesive according to any one of claims 1 to 6; 2) According to the type of binder obtained in step 1), a formula with a known binder content of the same type of binder is selected as a reference sample for thermogravimetric analysis to obtain a thermogravimetric TG curve and a differential thermogravimetric DTG curve; 3) The DTG curve of the reference sample is subjected to peak fitting processing to obtain the corresponding relationship between the peak area of ​​the fitting peak corresponding to the binder of different reference samples and the binder content; 4) The DTG curve of the sample to be tested is subjected to peak fitting processing to obtain the peak area of ​​the fitting peak corresponding to the binder of the sample to be tested; the binder content of the sample to be tested is obtained through the peak area of ​​the sample to be tested.

8. The test and analysis method for binder content according to claim 7, characterized in that: The conditions for peak fitting in steps 3) and 4) are independently: the weight loss temperature range corresponding to CMC is 200°C-300°C, the weight loss temperature range corresponding to SBR is 380°C-500°C, and the weight loss temperature range corresponding to PAA is 320°C-380°C.

9. The test and analysis method for binder content according to claim 7, characterized in that: The calculation method of step 4) is: CMC content M = a1 / a*m*100%, SBR content N = b1 / b*n*100%; PAA content Q = c1 / c*n*100%; Among them, a1, b1, c1 are the fitted peak areas of CMC, SBR, and PAA in the test sample after peak fitting; a, b, c are the fitted peak areas of CMC, SBR, and PAA in the reference sample after peak fitting, and m, n, and p are the contents of CMC, SBR, and PAA in the formula of the reference sample, respectively.

10. The test and analysis method for binder content according to claim 7, characterized in that: The reference sample and the sample to be tested were prepared in the same way; the reference sample and the sample to be tested were subjected to the same thermogravimetric analysis conditions.